Review on Resonator and Muffler Configuration Acoustics - KHAIRUDDIN, Muhammad Hariz; SAID, Mohd Farid Muhamad; DAHLAN, Afiq Aiman; KADIR, Khairuldean Abdul (Archives of Acoustics, 2018)
Nowadays, resonators are widely used in automobile, industrial applications, aerospace engineering, and some other fields. One of the unique characteristics of resonators which made them highly convenient is their acoustic capability to attenuate noise without having to use any acoustic absorptive material. The device acts by manipulating the sound waves to create mismatch impedance. Recent studies also suggest that the typical bulk size resonator with narrow frequency bandwidth is not the only option anymore, since there are newly designed resonators that are capable of having wide attenuation bandwidth and are smaller in size. Numerical and experimental measures were executed accordingly with the same purpose to obtain efficient noise attenuation results from varying resonators’ and mufflers’ configuration in terms of quantity, types, and geometry. The aim of this review is to summarize recent developments on resonator study and to try highlighting some noteworthy issues that need to be unraveled by future research. Helmholtz resonator, Quarter wave tube, Herschel-Quincke tube and helicoidal resonator are part of the numerous resonator studies that will be covered in this paper.